SEROPREVALENCE OF PORCINE CYSTICERCOSIS IN FOUR VILLAGES OF THE OMIA DISTRICT, AMAZONAS - Carhuallanqui P., Mijael (2010)
The cysticercosis is a zoonotic disease of world-wide distribution and in Peru represents the main parasitic zoonosis with 17 and 75% seroprevalence in humans and pigs respectively. The high seroprevalence indicates that Peru is an endemic area. The objective of this study was to obtain a representative level of infection with T. solium larvae in pigs of Omia, Nuevo Chirimoto, Mashuyacu and Tocuya villages, Omia district, Amazonas. Sampling was conducted in 48 animals, resulting 27.1% (13/48) of positives to the Electroimmuno Transference Blot (EITB) test. Data was analyzed in a program that uses stochastic simulations of the beta distribution (@Risk®) resulting in a mean seroprevalence of 28% with a distribution between 18.2 and 38.8%. Seroprevalence for Tocuya was 14.3% (0.8-39.3%), Nuevo Chirimoto was 4.8% (0.3-13.9%), Mashuyacu was 71.4% (50.5-88.7%), and Omia was 35.7% (16.6-57.2%), with statistical differences between villages. However, villages with higher values had better access routes and sanitary infrastructure, so it is assumed the existence of other factors that have intervened for the presentation of cysticercosis. None significant difference was found between age groups, sex, and rearing type in relation to the disease.